MOBILITAS PEKERJA PEMBANTU RUMAH TANGGA DARI DAERAH PINGGIRAN KE KOTA MEDAN (Studi Kasus di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang) - Muda, Indra (Universitas Medan Area, 2013)
Medan as one of the largest cities in Indonesia, the main attraction for the workers to earn a fortune coming from different regions. For workers who came from the outskirts of the city of Medan, most of them arrive in the morning and return late afternoon, while the others run to stay in Medan city in a matter of weeks or months. The problem in this study is, what are the factors that encourage mobility actors find work as a maid in the city of Medan. Is labor mobility affect female labor supply in the village. Is the Government District Percut Sei Tuan Deli Serdang taking action to reduce the rate of job mobility. Based on that research, the factors that drive mobility to the city of Medan is to supplement the family income or financial income. With the mobility of the population does not significantly affect the availability of labor in the village. District government's efforts Percut Sei Tuan to reduce the rate of mobility of people to the city of Medan was essentially no specific steps, only asked that the district government to travel to their place of work more carefully so it does not have an accident. The conclusion of this research is, the mobility of families due to economic factors, the availability of jobs in their village. Step Percut Sei Tuan district government to restrain the rate of mobility not only advised to be cautious road. For strengthening the rural economy, economic actors to connect capital district government with certain banks in the context of empowerment. District government through the Chief of the village should collect data on population mobility, then contact the users of their services in Medan that the perpetrators of mobility does not get abuse from her employer.